The reality of creative thinking strategies practice among Arabic language in the Directorate of Education South Hebron - Al-Sharha, Ashraf Ibraheem (Journal of Curriculum and Teaching Methodology, 2023)
This study aimed at identifying the reality of the practice of the Arabic language teachers in creative thinking strategies in the Directorate of Education/ South Hebron in the light of the variables (gender, specialization, school stage, academic qualification and years of experience), on a sample of (207) teachers (36%). A questionnaire was built to measure the reality of the Arabic language teachers ’practice of creative thinking strategies. It consisted of (32) items distributed into four areas: originality, fluency, flexibility and adding details, and the researcher made sure of the validity and reliability of the study tool, as the reliability coefficient reached (0.93). The study found a set of results that the degree of practice of Arabic language teachers in creative thinking in the Directorate of Education/ South Hebron is great. It also showed that there is no difference in the practice of creative thinking teachers in the Arabic language according to gender, specialization, scientific qualification and years of experience. While there is a difference of practice for the stage taught by the teacher and in favor of the upper basic stage. Based on the results, the study recommends holding training courses for Arabic language teachers in the production of educational aids and classroom management, enriching the Arabic language courses with literary texts from the eyes of Arabic literature that stimulate thinking, and reducing the job burdens placed on teachers to sharpen the creative energies of their students and cooperate with the local community in developing The infrastructure of schools and providing them with everything they need to cultivate the talents of students, such as libraries, theaters, and technological means, and encourage creative educational initiatives, and the adoption of university courses specialized in teaching creative thinking strategies.